Muscle strength and the risk of falls in community-dwelling elderly in Central Java in urban and rural areas - Nur Annisa; Dwi Rosella Komalasari (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2024)
Background: The elderly are individuals aged 60 and above, marking the final stage of the life cycle. The World Health Organization classifies the elderly into four groups: middle-aged elderly (45-59 years), elderly (60-74 years), older elderly (75-90 years), and very old elderly (above 90 years). Currently, there are 142 million people aged 60 and above in the 11 Southeast Asian WHO member countries. By 2050, this number is expected to triple, prompting the WHO to urge nations to prioritize aging on World Health Day. Decreased muscle strength for postural control is a risk factor for falls in the elderly, and a significant portion of falls may be attributed to this component. In Indonesia, the rate of fall-related injuries due to balance disorders is found to be 49.4% in individuals above 55 years, 67.1% in those above 65 years, and up to 35% in individuals between 70-75 years.Purpose: To determine the influence of muscle strength on the risk of falls in the elderly in urban and rural areas. Method: This study employed a cross-sectional study design, investigating the correlation between risk factors (independent) and outcomes (dependent) based on data collection through observations conducted at a single point in time. The research was conducted in Gonilan village as a representative urban area and Boyolali Regency, Central Java, as a representative rural area in August 2023. The study population included the elderly in Gonilan and Boyolali. Non-probability sampling with quota sampling was used, resulting in 204 participants meeting the survey criteria.Results: Muscle strength in urban areas with low categories had an odds ratio (OR) of -0.282, Exp B of 1.048, ρ-value of 0.824 with a 95% confidence interval (CI) of 0.962. In contrast, urban areas with high categories had an OR of 0.037, Exp B of 0.754, ρ-value of 0.310 with a 95% CI of 1.130. This indicates that the ρ-value for all areas is greater than 0.05, meaning there is no influence of muscle strength on the risk of falls in urban and rural areas.Conclusion: Based on the research findings, there is no influence of muscle strength on the risk of falls in the elderly in urban and rural areas. The risk of falls is influenced by various factors, including environmental conditions.